Long-Term Results of External Upper Esophageal Sphincter Myotomy for Oropharyngeal Dysphagia - Kos, Martijn P. (Springer-Verlag, 2009)
The aim of this work was to assess the efficacy of external myotomy of the upper esophageal sphincter (UES) for oropharyngeal dysphagia. In the period 1991–2006, 28 patients with longstanding dysphagia and/or aspiration problems of different etiologies underwent UES myotomy as a single surgical treatment. The main symptoms were difficulties in swallowing of a solid-food bolus, aspiration, and recurrent incidents of solid-food blockages. Pre- and postoperative manometry and videofluoroscopy were used to assess deglutition and aspiration. Outcome was defined as success in the case of complete relief or marked improvement of dysphagia and aspiration and as failure in the case of partial improvement or no improvement. Initial results showed success in 21 and failure in 7 patients. The best outcomes were observed in patients with dysphagia of unknown origin, noncancer-related iatrogenic etiology, and neuromuscular disease. No correlation was found between preoperative constrictor pharyngeal muscle activity and success rate. After follow-up of more than 1 year, 20 patients were marked as success and 3 as failure. All successful patients had full oral intake with a normal bolus consistency without clinically significant aspiration. We conclude that in select cases of oropharyngeal dysphagia success may be achieved by UES myotomy with restoration of oral intake of normal bolus consistency.